SAFETY INSPECTION OF PRESSURE VESSELS AT AN ENGINE GRINDER IN AGRESTINA-PE - de Queiroz Feitosa, Rômulo; Monaliza Cunha de Sousa, Aêda (Journal of Interdisciplinary Debates, 2023)
Pressure vessels are critical components in internal combustion engines as they withstand high pressures of oil, air, steam or other fluids. Failure of a pressure vessel can result in loss of containment, personal injury, equipment damage and, in severe cases, even explosions. Therefore, it is crucial to carry out periodic and rigorous inspections of these vessels in an engine overhaul to ensure their integrity and safety. This article discusses the steps of inspection in pressure vessels in an engine grinding plant, including inspection of pressure vessels containing argon gas stored to perform aluminum welding, as well as verification of design specifications, external visual evaluation, dimensional verification, ray inspection, visual inspection on compressors, which is important to extend its useful life and prevent accidents, inspection is performed according to specific standards and codes, such as ASME and API, and can be performed by internal or external inspectors, depending on the complexity of the equipment